2015
DOI: 10.1063/1.4927389
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer through metal-graphene interfaces

Abstract: The paper presents the results of Molecular Dynamics (MD) studies of the thermal properties of Cu and Ag composites with single- (SLG) and multi-layered (MLG) graphene. We show that the thermal boundary conductance (TBC) of the metal-graphene interface drops significantly for the systems containing more than one layer of graphene. It is also concluded that the TBC for a single graphene layer is significantly higher for silver than for copper. For both systems, however, we found that the interface is a barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Both Al and Au are expected to be physisorbed on the surface of graphene, which is theorized to results in a lower thermal boundary conductance compared to chemisorbed systems, such as Ni-and Ti-graphene. [5,6,10] From this, one can reasonably assume that the addition of functional groups that lead to a more hydrophilic surface, a typical indicator of improved adhesion between the metal film and graphene, should increase the thermal boundary conductance. The results of Fig.…”
Section: A Plasma Characterization and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Al and Au are expected to be physisorbed on the surface of graphene, which is theorized to results in a lower thermal boundary conductance compared to chemisorbed systems, such as Ni-and Ti-graphene. [5,6,10] From this, one can reasonably assume that the addition of functional groups that lead to a more hydrophilic surface, a typical indicator of improved adhesion between the metal film and graphene, should increase the thermal boundary conductance. The results of Fig.…”
Section: A Plasma Characterization and Processingmentioning
confidence: 99%
“…In other words, the thermal conductance (or resistance) across an interface depends on how easily free carriers pass through and/or vibrational modes couple across the interface of two materials. Not surprisingly then, the heat flow across graphene-metal interfaces is dependent upon the type of metal [5,6] and will be strongly affected by the interfacial roughness, [3,7] the presence of chemical defects, [8,9] the number of graphene layers [10], and the substrate on which graphene resides [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Wejrzanowski et al. 57 showed that the thermal boundary conductance (TBC) of the metal graphene interface dropped significantly for the systems containing more than one layer of graphene. It was also concluded that the TBC for a single graphene layer was significantly higher for silver than for copper.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TBC across Cu/single-layer graphene interfaces is about 10 MW m -2 K -1 [21] which is 1-3 order of magnitude lower than in pure metal [22], whereas the interfacial conducts between metal and c-axis for highly oriented pyrolytic graphite (HOPG) are similar to those of metals and diamond [23]. This fact is a huge obstacle in the production of composites based on metals with increased properties in which the effect of high in-plane conductivity of graphene can be used [24].…”
Section: Introductionmentioning
confidence: 98%